Motor Circuit-Specific Burst Patterns Drive Different Muscle and Behavior Patterns - Diehl, Florian (Society for Neuroscience, 2013)
In the isolated CNS, different modulatory inputs can enable one motor network to generate multiple output patterns. Thus far, however, few studies have established whether different modulatory inputs also enable a defined network to drive distinct muscle and movement patterns in vivo, much as they enable these distinctions in behavioral studies. This possibility is not a foregone conclusion, because additional influences present in vivo (e.g., sensory feedback, hormonal modulation) could alter the motor patterns. Additionally, rhythmic neuronal activity can be transformed into sustained muscle contractions, particularly in systems with slow muscle dynamics, as in the crab (Cancer borealis) stomatogastric system used here. We assessed whether two different versions of the biphasic (protraction, retraction) gastric mill (chewing) rhythm, triggered in the isolated stomatogastric system by the modulatory ventral cardiac neurons (VCNs) and postoesophageal commissure (POC) neurons, drive different muscle and movement patterns. One distinction between these rhythms is that the lateral gastric (LG) protractor motor neuron generates tonic bursts during the VCN rhythm, whereas its POC-rhythm bursts are divided into fast, rhythmic burstlets. Intracellular muscle fiber recordings and tension measurements show that the LG-innervated muscles retain the distinct VCN-LG and POC-LG neuron burst structures. Moreover, endoscope video recordings in vivo, during VCN-triggered and POC-triggered chewing, show that the lateral teeth protraction movements exhibit the same, distinct protraction patterns generated by LG in the isolated nervous system. Thus, the multifunctional nature of an identified motor network in the isolated CNS can be preserved in vivo, where it drives different muscle activity and movement patterns.